PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMPN 16 PADANG - Nugrah, Azzahra (Departemen Matematika, 2024)
Mathematical problem-solving proficiency is an important talent that math educators want to develop in their students. However, this ability in students is still very poor and substandard. Some people have proposed the CTL model as a way to overcome this problem. The purpose of this study is to compare the problem solving skills of eighth grade students at SMPN 16 Padang when taught Number Patterns using two different approaches: the conventional classroom method and the Contextual Teaching and Learning (CTL) approach. By using a control group that only participated in the post-test, this study used a quasi-experimental approach. When comparing the CTL model with the conventional model, eighth grade students at SMPN 16 Padang who used the CTL model showed better results.Keywords– Contextual Teaching and Learning, Conventional Learning, Mathematical Solving Ability